Comparison of linear and trochoidal milling for wear and vibration reduced machining - Gross, Daniel; Friedl, Fabian; Meier, Trixi; Hanenkamp, Nico (Procedia CIRP, 2020)
Vibrations during milling lead to frequent tool replacements. This results in an unsteady load on the machine, which leads to increased tool wear, poor surface quality and therefore strong economic and ecological burden. Self-excited vibrations are influenced by the machining conditions, such as the workpiece geometry or the tool path generated by the used computer-aided manufacturing (CAM) software. This article compares linear and trochoidal milling in terms of vibration behavior and resulting wear phenomena by machining different component geometries. The results show, that trochoidal milling is not a suitable strategy to reduce vibrations and tool wear compared to linear milling.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CAM; Milling; Milling strategy; Tool path optimazation; Vibration; Wear

Comparison of sprayability and solubility of bio-based lubricants with liquid carbon dioxide - Meier, Trixi; Gross, Daniel; Hanenkamp, Nico (MM Science Journal, 2021)
In recent years, cryogenic minimum quantity lubrication (CMQL) has been established in comparison to pure cryogenic cooling. The used oil has a crucial influence on the success of the technology. The aim of this study is to investigate the influence of oils from renewable resources with regard to their miscibility with carbon dioxide (CO2) and their spraying behavior. Ten different bio-based oils (synthetic ester, natural ester and fatty alcohol) have been examined regarding their suitability for CMQL compared to a conventional mineral hydrocrack oil. A validation based on sprayability and solubility properties with liquid CO2 has been performed. The sprayability and the resulting oil droplet size have an impact on the amount of oil entering the process zone and thus on the lubrication performance of the coolant concept. For this reason, a high-speed camera has been used to capture shadow images of the jet from an external cooling nozzle. In addition the width, intensity and uniformity of the oil application were evaluated. The solubility of the bio-based oils in CO2 is investigated in a static mixing chamber with varied mixing ratio. The miscibility of the bio-based oils in a single channel supply system was investigated with high-speed recordings of a dynamic mixing chamber. The results of the various experimental setups have been compared.<br
Keywords: CMQL; milling; turning; bio-based oils; carbon dioxide

ECO2il - Entwicklung biobasierter Metallbearbeitungsöle für die kryogene Minimalmengenschmierung : Schlussbericht zum Vorhaben : Laufzeit: 01.06.2019 bis 31.05.2022 - Meier, Trixi; Hanenkamp, Nico (2023)
Ein Großteil der spanenden Metallbearbeitungsprozesse wird aktuell durch große Mengen flüssiger Kühlschmierstoffe unterstützt. Aufgabe des Kühlschmierstoffs ist es, die Kühlung und Schmierung des Werkzeugs im Eingriff sicherzustellen sowie die Späne aus dem Bearbeitungsraum abzutransportieren. Die Anwendung konventioneller insbesondere wassermischbarer Kühlschmierstoffe in Zerspanungsprozessen wirkt sich negativ auf ökonomische und ökologische Faktoren sowie auf die Gesundheit der Mitarbeiter am Arbeitsplatz aus. Aus fertigungstechnischer Sicht stoßen konventionelle Kühlschmierstrategien bei der Bearbeitung neuartiger Hochleistungswerkstoffe an ihre Leistungsgrenzen. Ein Ansatz konventionelle Kühlschmierstoffe im spanenden Bearbeitungsprozess zu ersetzen bietet sowohl die Minimalmengenschmierung als auch die kryogene Kühlung mittels CO2. In diesem Projekt soll die Entwicklung biobasierter Schmierstoffe für die kryogene Zerspanung kombiniert mit Minimalmengenschmierung durchgeführt werden. Im Fokus stehen dabei Prozesse mit geometrisch bestimmter Schneide. Ziel ist es, anwendungsnah Schmierstoffe biologischen Ursprungs für die kryogene Minimalmengenschmierung zu entwickeln, diese bedarfsgerecht zu additivieren und zu optimieren. Dadurch soll sichergestellt werden, dass sowohl die Werkzeugstandzeit als auch Zeitspanvolumina im Vergleich zu konventioneller Überflutungskühlung gesteigert werden können. Die dadurch erreichbaren ökologischen Verbesserungen stellen den Kern dieses Projektes dar. Industrielle Anwender sollen dahingehend unterstützt werden, dass Bearbeitungsprozesse mit aktuell konventioneller Überflutungskühlung auf Minimalmengenschmierung in Kombination mit kryogener CO2 Kühlung umgestellt werden können. Dadurch werden sowohl ökonomische und ökologische Vorteile erzielt als auch die Leistungsfähigkeit der Fertigungsprozesse erhöh

Influence of Additivation of Bio-Based Lubricants on Sprayability and Solubility for Cryogenic Minimum Quantity Lubrication - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
The development of innovative cooling lubrication strategies is significantly driven by the need to machine materials resistant to high temperatures while taking into account both ecological and economic aspects. Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in the manufacturing process. A minimal amount of oil is added to the cryogenic medium carbon dioxide (CO2) to ensure both cooling and lubrication during tool engagement. In this context, vegetable oils, so-called triglycerides, can be used with respect to the cooling lubrication concept. The aim of this paper is to analyze various bio-based oils with regard to their solubility, spraying and flow behavior and to investigate the influence of additives on the performance. During the lubrication tests, the additives have shown no influence on the lubricating effects. Thus the chemical properties of the base oils primarily influence the properties with regard to solubility and spray behavior. Finally, the collected results were correlated with machining tests showing only a limited correlation with the aforementioned lubrication tests.
Keywords: CMQL; Milling; Liquid carbon dioxide; Bio-based lubricants

Influence of Carbon Dioxide Temperature on Sprayability and Solubility in Cryogenic Minimum Quantity Lubrication with Bio-Based Lubricants - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in many manufacturing processes. In previous series of experiments a variation of the thermodynamic state of the cryogenic medium taken from riser bottles could be observed. Consequently, the aim of this study was to specifically control the thermodynamic state of the CO2 and, associated with this, the density after removal from the riser bottles. To achieve this objective conventional cooling was implemented for the CO2 after withdrawal from the riser bundle in order to have a constant liquid state of the CO2 during feeding. The density of the cryogenic medium could be raised from ρ = 550 kg/m3 to over 800 kg/m at a mass flow rate of m˙ CO2 = 5 kg/h with the applied cooling method and can also be stabilized regarding the density pulsation. Subsequently, the effects of temperature-controlled CO2 on the sprayability and solubility in CMQL were examined and resulted in increased atomization of the oils and widening of the spray corridor with a greater main spray length and intensity. In addition stable conditions for the CMQL-supply to the manufacturing process were achieved by a lower pulsation of the CO2-oil mixture.
Keywords: CMQL; Liquid carbon dioxide; Bio-based lubricants

Investigation of Carbon Dioxide Based Blasting Technologies as Cryogenic Deburring Method for Titanium Alloy and Stainless Steel - Gross, Daniel; Heinz, Andrea; Amon, Sven; Meier, Trixi; Schmand, Ralf; Hanenkamp, Nico (Applied Mechanics and Materials, 2018)
This paper aims to expand the use of CO2 blasting by investigating a cryogenic deburring method for machined metallic materials. In advance to the actual deburring experiments, a streaming analysis based on high-speed video records was conducted for different blasting technologies, in order to gain deeper knowledge about their underlying active principles. For the titanium alloy Ti-6Al-4V and the stainless steel X6CrNiMoTi17-12-2, deburring experiments with three different blasting techniques were conducted and evaluated. It has been shown that cryogenic deburring has the potential to represent an alternative deburring solution for metals.
Keywords: cryogenic deburring; deburring with CO2; CO2-based blasting technologies; CO2 snow blasting; dry ice blasting

Investigation of lubricating oils from renewable resources for cryogenic minimum quantity lubrication - Meier, Trixi; Gross, Daniel; Hanenkamp, Nico (MM Science Journal, 2021)
Cryogenic minimum quantity lubrication using liquid carbon dioxide (CO2) has increasingly become the focus of research in recent years. With this cooling strategy it is possible to cool and lubricate the cutting zone individually by regulating the oil and liquid CO2 flow. The oil used has a significant influence on the process stability and performance. The aim of this study is to identify the influence of 15 different base oils from renewable sources on a milling process of X2CrNiMo17-12-2 with cryogenic minimum quantity lubrication. For this purpose, a non additivated sunflower, coconut and rapeseed oil and additional bio-based oils, such as synthetic ester and fatty alcohol, will be tested and compared to a conventional mineral oil regarding wear, process forces and productivity. In addition, the impact of the bio-based oils on rough turning of X2CrNiMo17-12-2 and finishing turning of 100Cr6 with cryogenic minimum quantity lubrication is evaluated and compared to the milling performance. The results have been analyzed in comparison to conventional emulsion flood cooling and recommendations have been given for the future development of sustainable lubricants to be applied with cryogenic cooling strateg
Keywords: CMQL; milling; turning; bio-based oils; carbon dioxide

Investigation of the effects of CO2 pre-cooling on the cooling capacity for cryogenic cooling in machining operations - Meier, Trixi; Selzam, Jan Harald; Röckelein, Andreas; Hanenkamp, Nico (CIRP Journal of Manufacturing Science and Technology, 2024)
Abstract: Liquid carbon dioxide (LCO2) based cryogenic cooling has shown promising results in terms of wear reduction, productivity increase and energy efficiency when machining high-temperature materials. For process-safe use with low pulsation, CO2 must be fed in the liquid state to cool the process zone. LCO2 is typically stored in riser bottles in which gaseous and liquid aggregate state coexist. A preliminary study has already shown that the liquefied state of the CO2 can be stabilized by pre-cooling. In this paper, the influence of a heat exchanger as a pre-cooling system on the cooling capacity of the CO2 is investigated and the required energy consumption is compared to unstabilized CO2, pressure increased CO2 and compressed air. It has been shown that pre-cooling leads to a more energy-efficient increase in the cooling capacity of the CO2 compared to pressure increased CO2. <br
Keywords: Cryogenic minimum quantity lubrication; Liquid carbon dioxide; Density enhancement; Cooling capacity; Machining; Energy effiency

Investigation of the influence of lubricating oils on the turning of metallic materials with cryogenic minimum quantity lubrication - Gross, Daniel; Bigelmaier, Matthias; Meier, Trixi; Amon, Sven; Ostrowicki, Nicolai; Hanenkamp, Nico (Procedia CIRP, 2019)
Nowadays, cooling and lubrication for cutting processes in industry are mostly based on flood cooling. The enormous quantities of lubricants are not only harmful for the environment and employees, but also require additional infrastructure and pre-treatment, while processed parts require an additional cleaning step due to metallic swarf which leads to high manufacturing costs. The cryogenic minimum quantity lubrication could serve as an alternative cooling and lubrication concept, which might be suitable for high-alloyed steels and titanium alloys as well. Within this work the potential of this new concept of cooling and lubrication was investigated by the utilization of different lubricants for turning of Ti6Al4V, X5CrNi18-10 and 42CrMo4 workpieces with a main focus on cutting forces, tool wear and resulting surface roughness. Required data indicates that the cryogenic minimum quantity lubrication might indeed be suitable to replace the conventional wet processing routes. The proper lubricants are selected to match the material to be machined.<br
Keywords: Turning; Cryogenic Machining; Minimum Quantity Lubrication; Ti6Al4V; 42CrMo4; X5CrNi18-10

Investigation of the influence of the additivation of a biological metalworking oil in cryogenic machining - Meier, Trixi; Seydaack, Milena; Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2022)